Physiological responses of the fan mussel Pinna nobilis to temperature: ecological and captivity implications - HERNANDIS, SEBASTIAN; IBARROLA, IRRINTZI; TENA-MEDIALDEA, JOSE; ALBENTOSA, MARINA; PRADO, PATRICIA; VÁZQUEZ-LUIS, MAITE; GARCÍA-MARCH, JOSE RAFAEL (Mediterranean Marine Science, 2023)
The fan mussel Pinna nobilis is experiencing a mass mortality event throughout the Mediterranean Sea. The survival of the remaining isolated populations and the maintenance and reproduction of individuals in captivity could determine the future of the species. This paper examines the clearance rate (CR) and oxygen consumption (VO2) of fan mussel individuals measured under 5 different temperatures (8.5, 14, 18, 23 and 28ºC). The measurements of both physiological variables revealed a threshold limit of thermal tolerance at both extreme temperatures, indicating the critical situation of the remaining populations, which are located in coastal lagoons and shallow bays where these extreme temperatures usually occur. Besides, the high clearance rates observed highlight the significant ecosystem service provided by the species in terms of water filtration, especially in confined waters with low renewal rates. Routine control of the clearance rate as an early warning system is proposed for detecting ailing individuals. Such a system could also be used to improve captivity conditions.